The Correlation Study among EFL Learners’ Reticence, Motivation and Speaking Habit - Lalu Wahyu Wiranata; Selamet Riadi Jaelani; Siti Maysuroh (LPPM Universitas Bumigora Mataram, 2023)
This research aims to investigate the correlation between students' reticence, motivation, and their speaking habits which effected their speaking skills. The method used is a quantitative approach with a correlational design. The population was the eleventh-grade students of MA NW Montong Kubur comprising one class with a total of 35 students. The researcher used the total sampling method, in which all eleventh-grade students became respondents. Data collection was done through questionnaire and speaking test. The results showed that the correlation coefficient between students' speaking anxiety and their speaking achievement was r=0.312. Although these two variables have a negative correlation, the value of r=0.312 can still be classified as a significant correlation. Furthermore, the correlation coefficient between students' motivation and their speaking habits was found to be r=0.032. This means that there is a positive relationship between these variables, but the value of r=0.032 indicates a low correlation. Finally, the results showed that the correlation coefficient between students' speaking reticence, motivation, and speaking habits was r=0.105 which means that these three variables have a positive correlation, although the value of 0.105 indicates a very low level of correlation.